A simple and efficient fluorescent probe for the rapid detection of H2S in living cells and on agar gels. Issue 22 (24th May 2017) - Li, Yaqian; Gu, Biao; Su, Wei; Duan, Xiaoli; Xu, Hai; Huang, Zhen; Li, Haitao; Yao, Shouzhuo
Abstract : Herein, a simple fluorescent probe, ( E )-1, 3, 3-trimethyl-2-(4-morpholinostyryl)-3 H -indol-1-ium iodide (Mi ), based on intramolecular charge transfer (ICT) was synthesized. Abstract : Herein, a simple fluorescent probe, ( E )-1, 3, 3-trimethyl-2-(4-morpholinostyryl)-3 H -indol-1-ium iodide (Mi ), based on intramolecular charge transfer (ICT) was synthesized. The probe can rapidly and sensitively sense hydrogen sulphide (H2 S) with low detection limit (15 nM). The reaction mechanism was investigated via fluorescence and mass spectra. Moreover, theMi probe was successfully used for the fluorescent imaging of H2 S in living cells, demonstrating its potential applications in biological science. Finally, agar gels based on theMi probe were fabricated, which could act as a solid optical sensor to conveniently and efficiently detect H2 S.